Clinical significance of extrathyroidal extension according to primary tumor size in papillary thyroid carcinoma. Issue 11 (November 2018) - Liu, Lihua; Oh, Chan; Heo, Jae Hyung; Park, Hee Sung; Lee, Kyungmin; Chang, Jae Won; Jung, Seung-Nam; Koo, Bon Seok
Abstract: Background: Extrathyroidal extension (ETE) is a risk factor for poor papillary thyroid carcinoma (PTC) outcomes. However, the clinical significance of ETE according to primary tumor size has not been well-established. The purpose of this study was to compare differences in clinical outcomes, according to the presence and extent of ETE, between different primary tumor size groups. Methods: In total, 381 patients with PTC underwent total thyroidectomy with or without lymph node (LN) dissection from 2004 to 2010. We divided the patients into two groups according to primary tumor size: ≤ 1 cm or >1 cm. Each group was further divided into subgroups according to the presence of ETE (ETE vs. no ETE) and degree of ETE (microscopic ETE vs. macroscopic ETE). The clinicopathological features and rate of recurrence during follow-up were compared among groups. Results: Among the PTC patients with primary tumors >1 cm, patients with ETE had a higher recurrence rate than those without ETE, and only macroscopic ETE affected recurrence in patients with PTC > 1 cm ( P < 0.05). However, there was no significant difference in recurrence rates between those without ETE and those with microscopic ETE ( P = 0.100). When the primary tumor size was less than 1 cm, there were no difference in recurrence rates between the groups with or without ETE, or between the groups with microscopic and macroscopic ETE ( P > 0.05). Conclusions: Our data suggests that the presence and degree of ETE may be associated with PTC outcome based on primary tumor size.